Three-dimensional pore characterization of intact loess and compacted loess with micron scale computed tomography and mercury intrusion porosimetry - Linxin Zhang (Nature Portfolio, 2020)
Abstract The pore structure is one of the most important properties of soil, which can directly affect the other properties such as water content, permeability and strength. It is of great significance to study the soil pore structure for agricultural cultivation, water and soil conservation and engineering construction. This paper investigates the 3D pore characterization of intact loess and four kinds of compacted loess (with different dry density) in northwest China. Micro scale computed tomography and mercury intrusion porosimetry tests were performed to get the porosity, specific surface area, pore size distribution, connected pores content and isolated pores content of different samples. Results show that the intact loess has more connected pores than the compacted loess, and the compacted loess whose dry density appears to be modelled well still have different pore structure with the intact loess. In addition, as the compactness increasing, the large pores (>13 μm) were firstly broken into medium pores (8~13 μm) and some small pores (<8 μm) until the pore structure was close to the natural structure of the intact loess, after that medium pores began to be broken into small pores.